2000
DOI: 10.1007/s100520050026
|View full text |Cite
|
Sign up to set email alerts
|

Structure function of the nucleus in the perturbative QCD with $N_c\rightarrow\infty$ (BFKL pomeron fan diagrams)

Abstract: Equation for the sum of BFKL pomeron fan diagrams is rederived by direct summation and solved numerically for rapidities y ≤ 50. At high rapidities y > 20 the resulting crosssections for the scattering of a longitudinally polarized qq pair on the nucleus cease to depend on its transverse dimension and tend to a constant limit 0.1768 R 2 A , which corresponds to scattering of a colour dipole on a black disk. Thus the unitarity is restored and the singularity in the j plane is reduced to a simple pole at j = 1. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
241
2
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(262 citation statements)
references
References 3 publications
13
241
2
6
Order By: Relevance
“…Such prescriptions have been assumed in all numerical simulation of the BK equation [33,45,[72][73][74][75][76][77]. Similar assumptions were used in the analytical estimates of Ref.…”
Section: What We Mean By Running Couplingmentioning
confidence: 99%
“…Such prescriptions have been assumed in all numerical simulation of the BK equation [33,45,[72][73][74][75][76][77]. Similar assumptions were used in the analytical estimates of Ref.…”
Section: What We Mean By Running Couplingmentioning
confidence: 99%
“…For fan diagrams Fig. 2, left, there exists an alternative derivation in the dipole picture, which, translated into the BFKL language, indicated that indeed in consecutive splittings exactly vertices Γ appear [13,14]. However in view of the rather indirect correspondence between the dipole and BFKL approaches it would be desirable to derive this result within the latter approach.…”
Section: Motivationmentioning
confidence: 98%
“…the scattering of a projectile on three color singlet targets. In earlier demonstrations [14] it was tacitly assumed that in consecutive splittings exactly the same vertices Γ appear. An explicit derivation, however, is still missing.…”
Section: ←2mentioning
confidence: 99%